Historical Context of Research Universities in Thailand - Rungfamai, Kreangchai (SUSURGALUR, 2013)
ABSTRACT: This paper is intended to examine the historical context of research universities in Thailand. The historical examination of research universities in Thailand is conceptualized through three critical incidents in Thai modern history. In the first incident of embracing Western knowledge, the first university in the Western sense was established. The main function of the university during this period was to produce civil servants to serve the establishment of the modern bureaucracy. In the second phase of political alliance with the USA (United States of America) and the government policy of economic development, the term research had become substantially embraced, particularly within the university. And in the third phase of the forces of globalization on higher education, the research function for a number of Thai universities has increasingly emphasized for different purposes. In addition, the Asian financial crisis in 1997 has become one of the key driving factors in the reforms of higher education governance arrangements and university funding in Thailand. Finally, the implementation of the National Research University project in 2009 has triggered the university to be more proactive towards the research function. KEY WORD: Research universities in Thailand, historical context, Western knowledge, political alliance with the USA, and globalization.IKHTISAR: Makalah ini berjudul âKonteks Historis Universitas-universitas Riset di Thailandâ. Ianya dimaksudkan untuk menguji konteks historis universitas riset di Thailand. Pengkajian sejarah universitas riset di Thailand dikonseptualisasikan melalui tiga kejadian penting dalam sejarah modern Thailand. Dalam kejadian pertama yang merangkul pengetahuan Barat, universitas pertama dalam pengertian Barat didirikan. Fungsi utama dari universitas selama periode ini adalah menghasilkan PNS (Pegawai Negeri Sipil) untuk melayani pembentukan birokrasi modern. Pada tahap kedua dimana aliansi politik dengan USA (Amerika Serikat) dan kebijakan pemerintah terhadap pembangunan ekonomi, terminologi penelitian telah berkembang secara substansial, khususnya di lingkungan universitas. Dan dalam fase ketiga dari kekuatan globalisasi pada pendidikan tinggi, fungsi riset untuk sejumlah perguruan tinggi di Thailand telah semakin ditekankan untuk tujuan yang berbeda. Selain itu, krisis moneter di Asia pada tahun 1997 telah menjadi salah satu faktor pendorong bagi kunci reformasi tentang pengaturan tata-kelola pendidikan tinggi dan pendanaan universitas di Thailand. Akhirnya, pelaksanaan proyek Universitas Riset Nasional pada tahun 2009 telah memicu universitas untuk lebih proaktif terhadap fungsi penelitian.KATA KUNCI: Universitas riset di Thailand, konteks historis, pengetahuan Barat, aliansi politik dengan Amerika Serikat, dan globalisasi.About the Author: Kreangchai Rungfamai, Ph.D. is a Senior Policy Researcher at the National Science Technology and Innovation Policy Office in Thailand. For academic purposes, the author can be contacted via his e-mail address at: kreangchai_tdai@hotmail.comHow to cite this article? Rungfamai, Kreangchai. (2013). âHistorical Context of Research Universities in Thailandâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.1(2), September, pp.103-112. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808, ISSN 2302-5808. Chronicle of the article: Accepted (July 15, 2013); Revised (August 15, 2013); and Published (September 30, 2013).